Elastyczność strategiczna - jej konceptualizacja i sposoby osiągania w praktyce - Osbert-Pociecha, Grażyna (Strategic Flexibility - Conceptual Framework and Ways of Accomplishi, 2008)
The need of "being flexibile" becomes more and more essential for an organization also in strategic dimension. This article includes the reviewing and analysing of concept strategic flexibility which basis on literature. Ultimately the essence of flexibility is interpreted as a way from trade off to trade up and some example of achieving the strategic flexibility is showed.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 278-286